Medical negligence: current position of Malaysia and Bangladesh - Islam, Md. Zahidul (World Journal of Environmental Biosciences, 2019)
Negligence in the medical field refers to a breach of a duty to take reasonable care towards the patient, and as a result of that breach, the patient suffer damage. Medical negligence by doctors is a violation of right to health which is granted by the constitution of Malaysia and Bangladesh. To protect the health of the citizen, many develop countries have enacted and established special laws but in Bangladesh and Malaysia, there is no special laws related to medical negligence. The main purpose of this paper is to focus current challenges of medical negligence in Malaysia and Bangladesh and to discuss the current laws related to medical negligence. The article also attempts to focus the reforming the existing system. It is qualitative research and comparative research. Primary and secondary resources are used in this paper. The information has been taken from many readings, articles, books, case law and status. The result is that Bangladesh and Malaysia is following Medical Negligence from long time ago. We have many problems to solve this situation. The issue is more dynamic in a society like Malaysia and Bangladesh where the issue of medical negligence is still consider to be the result mishap and people illogically believe accept that the impact of medical negligence is consider in some cases to be the result of sin on the part of the parents of the patients. It is expected that the present study assist to simplify improvement of the legal regime of the Medical Negligence and the implementation of laws for the better future of the Medical Negligence of Bangladesh and Malaysia.